Croatian-Slavonian Estates in the Sixteenth Century in Central and South-East European Regional Context - Štefanec, Nataša (Array, 2009)
The authoress compared the functioning of the Inner-Austrian, Croatian and Slavonian Estates challenged by the Ottoman penetration in the period of the 'state making.' Inner-Austrian military authorities took the initiative in the organization of the Croatian and Slavonian Military Border. Through political and religious struggles with the Archduke, the Inner-Austrian Estates improved their overall political and military influence in their Lands and wider region managing to establish and administer a complex defence system in front of their own territory. Financially exhausted and directly endangered by the Ottomans, the Croatian and Slavonian Estates were not able to make a better use of their remaining resources and to create a constructive negotiating position with regard to the Inner-Austrians. They were mainly concerned with the preservation of their municipal privileges in a situation that required new solutions as an answer to various threats, which resulted in military and political marginalization in the region.